Civil Society and Democracy in Latin America (Palgrave Macmilan, 2006)
A dense web of private associations drawn from multiple social classes, interest groups and value communities makes for a firm foundation for strong democracy. In Latin America today, will civil society improve the quality of democracy or will it foster political polarization and reverse recent progress? Distinguished theorists from the United States, Canada and Latin America explore the diverse impact of civil society on economic performance, political parties, and state institutions. In-depth and up-to-date country studies explore the consequences of civil society for the durability of democracy in three highly dynamic, controversial settings: Argentina, Brazil and Venezuela.